Population pharmacokinetic study of ceftriaxone in elderly patients, using cystatin C-based estimates of renal function to account for frailty - Tan, S.J.; Cockcroft, M.; Page-Sharp, Madhu; Arendts, G.; Davis, T.M.E.; Moore, Brioni; Batty, Kevin; Salman, S.; Manning, L. (AMER SOC MICROBIOLOGY, 2020)
Ceftriaxone is widely used for respiratory and urinary infections in elderly and frail patients, but there are few pharmacokinetic studies. A prospective population pharmacokinetic study of ceftriaxone in adults over 65 years old was undertaken. Dried blood spots collected at baseline (predose) and 0.5, 1, 4, 8, and 24 h after administration of 1 g of ceftriaxone were assayed using a validated liquid chromatography-mass spectroscopy analytical method. Frailty was classified using the Edmonton frailty scale and grip strength via a hand dynamometer. Estimates of glomerular filtration rate were determined using creatinine-based and cystatin C-based equations. Of 26 patients recruited, 23 (88%) were vulnerable or very frail. Estimates of drug clearance improved significantly with a cystatin C-based estimate of renal function that accounted for frailty. Simulations indicate that the combined effects of ranges of size and renal function resulted in a 6-fold range in peak ceftriaxone concentrations and 9-fold range in total exposure (area under the concentration-time curve [AUC]). For elderly patients with moderate or severe renal impairment, 48-h dosing results in greater trough concentrations and total exposure than the trough concentrations and total exposure in patients with normal renal function receiving 24-h dosing. Cystatin C-based measures of renal function improved predictions of ceftriaxone clearance in elderly patients.